2019
DOI: 10.1177/0192513x19860182
|View full text |Cite
|
Sign up to set email alerts
|

Parental Dissatisfaction, Health, and Well-Being Among Older Chinese Adults: The Mediating Role of Self-Esteem and Feeling Useless

Abstract: Little work has considered the relationship between parental dissatisfaction and health and well-being among older adults. This study investigates whether parental dissatisfaction is linked to four health and well-being outcomes and whether the proposed associations are partly mediated by self-esteem and feeling useless in a 2014 sample of 432 community-dwelling older Chinese parents aged 60 to 79 years. Results from logistic and ordinary least squares regression modeling show that parental dissatisfaction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…The increase in self‐esteem during the SGP, however, predicted a decrease in negative affect and an increase in positive affect. These results are in line with previous evidence of an association between self‐esteem and SWB in older adults (Hajek & König, 2019; Yang & Wen, 2019), and also with Ryff's (1989) proposal of self‐acceptance as the most recurrent criteria of well‐being.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in self‐esteem during the SGP, however, predicted a decrease in negative affect and an increase in positive affect. These results are in line with previous evidence of an association between self‐esteem and SWB in older adults (Hajek & König, 2019; Yang & Wen, 2019), and also with Ryff's (1989) proposal of self‐acceptance as the most recurrent criteria of well‐being.…”
Section: Discussionsupporting
confidence: 92%
“…The most recurrent criterion of well‐being according to Carol Ryff (1989) is self‐acceptance, measured as self‐esteem, the degree to which the qualities and characteristics contained in one's self‐concept are perceived to be positive. Yang and Wen (2019) further highlighted the close association between self‐esteem and well‐being in older adults, showing how life satisfaction is mediated by self‐esteem and feelings of uselessness. Ronzi et al (2018) suggested that self‐esteem can be a mediator between participating in SGPs and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported health has been shown to be a good proxy for measuring health status and a reliable technique as a predictor of mortality [ 69 ]. To avoid much-skewed distribution of responses [ 70 ], we dichotomized the responses as done in previous studies [ 5 , 64 , 71 , 72 ]. Respondents who answered very good and good were categorized as having “good self-reported health”, while those who answered fair, bad, and very bad were categorized as having “poor self-reported health”.…”
Section: Methodsmentioning
confidence: 99%